Spontaneous Pneumomediastinum: A Rare Cause of Chest Pain - Barroso, Daniela (2023)
Spontaneous pneumomediastinum is a rare medical condition characterized by the presence of free air in the mediastinum, not preceded by trauma, surgery, or another medical procedure. It predominantly affects young adult males and usually has a benign course, and in most cases, it is not possible to identify the precipitating factor. There are some conditions that predispose to its occurrence, namely those that lead to an increase in intrapleural pressure, such as coughing, vomiting, or vigorous exercise. We report a case of a 21-year-old male who presented with acute-onset shortness of breath after an episode of coughing and was found to have mediastinal and subcutaneous emphysema. Clinical, laboratory, and radiological studies did not demonstrate any predisposing factor, and the case was classified as spontaneous pneumomediastinum